Cupping Therapy: An Overview from a Modern Medicine Perspective - Tamer S. Aboushanab; Saud AlSanad (Medical Association of Pharmacopuncture Institute, 2018)
Cupping therapy is an ancient traditional and complementary medicine practice. Recently, there is growing evidence of its potential benefits in the treatment of pain-related diseases. This article gives an overview of cupping therapy practice. Furthermore, this article suggests a new classification of cupping therapy sets, a new classification of cupping therapy adverse events, and an updated classification of cupping therapy types. Keywords: Cupping therapy, Hijama, Types, Classification, Adverse events, Indications